Systematic Literature Review on Web Performance Testing - Legramante, Guilherme; Bernardino, Maicon; Rodrigues, Elder Macedo; Basso, Fábio (Anais da Escola Regional de Engenharia de Software (ERES); 2020: Anais da IV Escola Regional de Engenharia de Software, 2020)
Performance Testing is essential to ensure the quality and scalability of Web applications. A well-defined process may guide Performance Testing Engineer in conducting this task. We intended to enlighten some major inputs related to web performance testing. For this, we have formulated and executed a given protocol, according to the Systematic Literature Review (SLR) protocol in Software Engineering. So, 37 papers were selected/analyzed and we have extracted their most relevant contribution in order to answer our research questions. This analysis enabled us discovering preeminent performance testing profiles/roles, approaches, artifacts, methods, stages or phases and activity flows that have been reported in the literature. We believe that, despite those several studies that mapping performance test context, there are a few remarks in which a clarification might be needed, once there is no well-established process that comprises the whole activities mapped as well as established a relation with other studies. Therefore, this study intends to provide relevant input that one may establish a novel web performance testing process.